Corporate Transfer Policy. Comparative Reaction of Managers and their Spouses - Pinder, Craig (Relations industrielles / Industrial Relations, 1978)
This study examines the relative importance of specific transfer policy provisions in determining overall transfer policy satisfaction ; the similarities and differences between managers and their spouses in terms of their attitudes concerning these specific provisions, and age differences among managers as they correlate